Allah our creator - Nazlee,, sajda (Goodwood Books; India, 2010)
Allah Our Creator explores the concept of God$1 (Bs creation in Islam, emphasizing His power, wisdom, and the intricate beauty of the world as a reflection of divine design and purpose.s